Advanced Sensor Systems and Applications XII 2022
DOI: 10.1117/12.2643054
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics of coupled gratings at PT-symmetry and its destruction

Abstract: The article describes an optical response of metastructure consisted of two optically coupled resonant subwavelength rectangular -profile diffraction gratings, between which a layer of optically transparent dielectric was placed. The features of optical resonance transmittance and reflectance for optical PT-symmetry mode was numerical investigated and some advantages of using optical PT-symmetry for resonance transmittance (reflectance) improving was demonstrated. The spectral characteristics of the metastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this case, the greatest influence on the response of the structure under study is exerted not directly by the deviation of the values of the gain and loss levels, but by their mismatch. In particular, in previous studies, we have shown that a mismatch of the loss and gain levels of gratings by more than 10% reduces the gain of the radiation passing through the system by about 520 times, and increases the spectral linewidth by about 120 times [31]. In this case, it is expected that in practice the mismatch between loss and gain levels will be several times smaller.…”
Section: Active System With Dispersion In the Optical Pt-symmetry Modementioning
confidence: 83%
See 1 more Smart Citation
“…In this case, the greatest influence on the response of the structure under study is exerted not directly by the deviation of the values of the gain and loss levels, but by their mismatch. In particular, in previous studies, we have shown that a mismatch of the loss and gain levels of gratings by more than 10% reduces the gain of the radiation passing through the system by about 520 times, and increases the spectral linewidth by about 120 times [31]. In this case, it is expected that in practice the mismatch between loss and gain levels will be several times smaller.…”
Section: Active System With Dispersion In the Optical Pt-symmetry Modementioning
confidence: 83%
“…Obviously, in the region where absorption is significant, the efficiency of subwavelength resonant structures will be much lower, but the use of an active (inverted) medium in one of the waveguide subwavelength periodic channels can compensate for the losses [31]. As will be shown further, compensation for losses and amplification in such a system are possible even when the imaginary part of the refractive index of the active grating does not exceed in magnitude that of a lossy symmetric grating.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, for greater simplicity and clarity, for the active lattice 3 (in order not to be distracted by the development and description of the pumping mechanism), some abstract material was used in most of its properties identical to silicon, but it is possible to control the imaginary part of its refractive index (for example, by changing the level of optical pumping).Further in the article, the value of the imaginary part of the refractive index of item 3 n3Im will be expressed in terms of fractions of the imaginary part of the refractive index of the item 4 (active) n4Im: n3Im = -An4Im, where A is the corresponding dimensionless coefficient. The geometric parameters of the matastructure were set the same as in previous studies [17,18]: the height of the gratings is 60 nm, the period of the lattice strokes is 320 nm, the filling coefficient of the gratings is 0.6, the layer height between the structured layers is 630 nm. As it was demonstrated earlier, at these parameter values, α = 0 and A = 1 (n3Im = -n4Im), the system probably is located near a singular point (the point of phase transition from state with PT-symmetry to a state with destroyed PT-symmetry).…”
Section: Inclination Angle On a Metasurface With Pt-symmetry Propertiesmentioning
confidence: 99%
“…Consider the proposed idea on the example of a previously developed metastructure with PT-symmetry properties [17,18]. The metastructure is formed by two optically coupled subwavelength diffraction gratings with a rectangular stroke profile, one of which (passive) is characterized by losses, and the other (active) by gain (see Fig.…”
Section: Inclination Angle On a Metasurface With Pt-symmetry Propertiesmentioning
confidence: 99%